1971
DOI: 10.1002/app.1971.070150103
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of mechanisms of synergistic interactions in PVC stabilization

Abstract: synopsisSynergism in poly(viny1 chloride) stabilization has been studied by measuring rates of hydrogen chloride evolution from samples of polymer in the presence of stabilizers in di-(a-ethylhexyl) phthalate solution in an inert atmosphere. Barium, cadmium, calcium, and zinc laurates, when used alone, allow escape of hydrogen chloride well before stoichiometric uptake is achieved, whereas synergistic mixtures of calcium-zinc and barium-cadmium laurates absorb almost the theoretical quantity of hydrogen chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Pentaerythritol (Pe) is an important secondary stabilizer which forms complexes with zinc chloride to delay the appearance of ‘zinc burning’ [15]. Briggs and Wood [16] and Wang et al [17] reported that Pe had some synergistic effect with CaSt 2 /ZnSt 2 caused by the formation of undetermined complexes with the reaction products of calcium and zinc stearates. Abbås and Sörvik [18] considered that the excellent static stability caused by Pe might be partly attributed to its direct reaction with HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Pentaerythritol (Pe) is an important secondary stabilizer which forms complexes with zinc chloride to delay the appearance of ‘zinc burning’ [15]. Briggs and Wood [16] and Wang et al [17] reported that Pe had some synergistic effect with CaSt 2 /ZnSt 2 caused by the formation of undetermined complexes with the reaction products of calcium and zinc stearates. Abbås and Sörvik [18] considered that the excellent static stability caused by Pe might be partly attributed to its direct reaction with HCl.…”
Section: Introductionmentioning
confidence: 99%
“…24 From this discussion we can already observe the possibility that various forms of stabilizer reaction products with HCl may react among themselves. Possibilities for a reaction of this type were mentioned in so many papers [7][8][9][25][26][27][28] (although without proof, as found elsewhere 13 ) that there is little doubt that this is a true mechanism of PVC stabilization. Possibilities for a reaction of this type were mentioned in so many papers [7][8][9][25][26][27][28] (although without proof, as found elsewhere 13 ) that there is little doubt that this is a true mechanism of PVC stabilization.…”
Section: Functions Of Pvc Stabilizersmentioning
confidence: 99%
“…Phosphites are thought to be able to react with zinc chloride according to the scheme below: 8,23 The only other known reaction of metal chlorides has been discussed in Section 11.1 with exchange of chlorine between zinc or cadmium chlorides and carboxylates of calcium and barium, respectively. Phosphites are thought to be able to react with zinc chloride according to the scheme below: 8,23 The only other known reaction of metal chlorides has been discussed in Section 11.1 with exchange of chlorine between zinc or cadmium chlorides and carboxylates of calcium and barium, respectively.…”
Section: Functions Of Pvc Stabilizersmentioning
confidence: 99%
See 2 more Smart Citations